Effect of once‐daily indacaterol in a predominantly Chinese population with chronic obstructive pulmonary disease: A 26‐week Asia‐Pacific study. (3rd January 2014) - Yao, Wanzhen; Wang, Changzheng; Zhong, Nanshan; Han, Xiaowen; Wu, Changgui; Yan, Xixin; Chen, Ping; Yang, Wei; Henley, Michelle; Kramer, Benjamin
Abstract: Background and objective: This study, in a predominantly Chinese population, investigated the efficacy and safety of a once‐daily (o.d.) inhaled ultra‐long‐acting β2 ‐agonist indacaterol for the treatment of moderate‐to‐severe chronic obstructive pulmonary disease (COPD). Methods: This is a 26‐week, double‐blind study on randomized patients who received indacaterol 150 μg or 300 μg or placebo o.d. The primary variable was trough forced expiratory volume in 1 s (FEV1, average of 23 h 10 min and 23 h 45 min post‐dose values) at Week 12. Health status (St George's Respiratory Questionnaire, SGRQ), dyspnoea (transition dyspnoea index, TDI) and safety were evaluated over 26 weeks. Results: Of the 563 patients randomized, 561 (89.8% Chinese) received treatment and 482 completed. At Week 12, trough FEV1 improved significantly for indacaterol 150 and 300 μg versus placebo (1.32, 1.29 vs 1.17; P  < 0.001 for both comparisons), with differences exceeding the pre‐specified minimal clinically important difference of 0.12 L. At Week 26, TDI score was superior to placebo for indacaterol 150 and 300 μg (0.82, 1.15; P  < 0.01), as was the percentage of patients with a clinically relevant improvement (≥1 point) (74.1%, 78.6% vs 55.5%; P  < 0.05). Both doses provided ≥4‐point improvements from baseline in SGRQ score at Week 26 that were numerically greater than placebo (unadjusted means: −9.6, −8.8 vs −7.0), with a similar pattern in percentage of patients with clinically relevant improvements in SGRQ score (65.0%, 61.5% vs 60.6%). Incidences of adverse events were comparable across treatment groups. Conclusions: Indacaterol delivered effective bronchodilation with significant improvements in breathlessness and health status in this predominantly Chinese population. Abstract : We investigated the effect of indacaterol on FEV1, dyspnoea and health‐related quality of life in a predominantly Chinese population diagnosed with moderate‐to‐severe COPD. Indacaterol proved to be a useful treatment option as it showed effective bronchodilation and improvements in breathlessness and health status in this population.